Rise of the machines: Normothermic regional perfusion use in heart transplantation in the United States - Gouchoe, Doug A; Satija, Divyaam; Cui, Ervin Y; Schroder, Jacob N; Milano, Carmelo A; Bishawi, Muath; Alvarez, Ammu V; Choi, Kukbin; Henn, Matthew C; Lampert, Brent C; Mokadam, Nahush A; Whitson, Bryan A; et al. (The Journal of thoracic and cardiovascular surgery, 2025)
Normothermic regional perfusion (NRP) and direct procurement and perfusion (DPP) allow for transplantation with donation after circulatory death (DCD) hearts. This study aimed to characterize the use of and variations in NRP and DPP for DCD transplants in the United States. Heart transplants performed between December 1, 2019 and March 31, 2024, were identified from the United Network for Organ Sharing database. DPP and NRP procurement strategies were classified based on previously published methods. The groups were compared, and survival was assessed using Kaplan-Meier methods. Geographic and center variability was categorized using encrypted data. There were 595 NRP transplants and 625 DPP transplants. Distance traveled and out-of-body time were significantly lower for the NRP group (P < .01 for both). There were no significant differences in postoperative dialysis, stroke, or 1-year survival between the 2 groups; however, the rate of postoperative pacemaker placement was higher with NRP (P < .05). From 2019 to 2024, 54 of 61 centers (88.5%) used NRP, 50 of 61 centers (82%) used DPP, and 43 of 61 centers (70.5%) used both procurement techniques, with NRP the more popular DCD procurement technique. Geographically, NRP was more prevalent in regions 2, 5, and 8 used, whereas DPP was most prevalent in regions 1, 3, and 10. The use of NRP is increasing in the United States, with tremendous growth seen since its introduction several years ago. Significant variation remains in the use of NRP and DPP, and further exploration of the impact of each procurement and preservation strategy on transplantation outcomes is needed.